TOWARD AN ETHICAL SOUNDSCAPES: COMPARING INTERNATIONAL AND NATIONAL NOISE REGULATIONS IN PUBLIC SPACES - Pratisti, Siti Aliyuna (Aliansi, 2025)
Ethical soundscapes refer to sound management in public spaces emphasizing individual rights and high respect toward cultural differences. Indonesia, with a high level of noise pollution from traffic and other human activities, is among countries that are facing challenges in maintaining an ethical sound in the public sphere. While regulations existed, such as regulation for broadcasting Azan, a more comprehensive regulation is still far from being openly discussed. Theories of ethical soundscapes and the public sphere are used as guidelines in discussing Indonesia’s problem of unregulated noise. As for the method, this research employed a literature study on noise regulations to get a broad and systematic view of ethical soundscapes at national and international levels. The result shows that despite existing regulations, the lack of public awareness of the well-being threats caused by noise pollution poses as main challenge in realizing the ethical soundscapes in Indonesia. While finding indicate that dissemination of noise pollution regulations is essential, mainly by promoting constructive discourse at the communities’ level.